Curriculum Construction for the Education of Indonesian Migrant Workers’ Children in Malaysia - Kuswandi, Iwan; Ridwan, M.; Surur, Miftahus; Shohenuddin, Shohenuddin; Asmoni, Asmoni (Jurnal Pendidikan Progresif, 2024)
Curriculum Construction for the Education of Indonesian Migrant Workers' Children in Malaysia. Curriculum is one of the essential elements of the education system. In the learning process, the curriculum must be developed innovatively to continue to follow the development flow. There are many types of curriculum development models, one of which is the Hilda Taba development model. The Hilda Taba development model focuses more on teacher attention when developing the educational curriculum used in an academic institution. The research method used in this study is qualitative, with a case study approach. This study examines the curriculum construction at the Guidance Center of the Indonesian School of Kuala Lumpur (SIKL) through the lens of Taba's curriculum development theory. Moreover, this study employs a case-based qualitative method, with an educational anthropology approach. Data were collected through observation, interviews, and documentation. Furthermore, the analysis utilized an interactive model, incorporating data collection, condensation, presentation, and verification of conclusions. To sum up, the teacher’s role is crucial in organizing education at the Guidance Center. The purpose of this education is to eradicate illiteracy, involving the Merdeka Curriculum and 2013 Curriculum materials. In the meantime, the education process is organized by class levels, starting from class 1 to class 6, with an additional so-called calistung class. Evaluation is through exams at each Guidance Center, with exam materials provided by the Indonesian School of Kuala Lumpur. Keywords: curriculum, children, indonesian migrant workers.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024146